The Effectiveness of a Proposed Program Based on Stepanz's Model of Changing the Alternative Chemical Concepts on the Achievement of Ninth-Grade Students in Jordan - Basil A. Husein (Sultan Qaboos University, 2015)
This quasi-experimental study aimed to investigate the effect of Stepanz' model in changing the alternative chemical concepts on the achievement of ninth-grade students. The participants of the study were 50 ninth grade male students who were distributed randomly into two groups: experimental group and control group. To answer the question of study, data was gathered and analyzed using (T-test). The results showed that there were statistically significant differences (p. < 0.05). In students mean scores with regards to their achievement. Those differences were in favor of the students who were taught using Stepanz model. In light of these results, the researcher recommend adopting Stepanz model in the teaching -learning process and training in-service teachers and reforming the scientific subjects in accordance with this model. In addition, the researcher recommends that more researches to be conducted to examine the effect of Stepanz model in changing the alternative chemical concepts on the achievement of students at different grade levels and in other subjects.